Machine Learning and Explainable AI for Parkinson’s Disease Prediction: A Systematic Review - Ndlovu, Belinda; Maguraushe, Kudakwashe; Mabikwa, Otis (AI Society & STMIK Indonesia, 2025)
Parkinson's disease is a movement disorder within the nervous system that impacts millions of people across the world. The standard diagnostic methods usually miss early subtle signs of disease which has driven research into Machine Learning (ML) and Explainable Artificial Intelligence (XAI) to develop better predictive models. Following PRISMA guidelines we analyzed 13 studies found in IEEE Xplore, PubMed and ACM concerning different ML methodologies for Parkinson’s disease prediction. Deep learning models using vocal and motor data achieve good accuracy but require more clinical trust and transparency due to their opaque